Analisis Perspektif Lingkungan Pembelajaran Mahasiswa Tingkat Pertama Perguruan Tinggi - Nurmalita, Rahma; Nur'aini, Ruhul Aflah; Hasyim, Nur Wakhid (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to analyze the perspectives of a university or college-level classroom learning instrument, the college and university classroom environment inventory (CUCEI), and then use it to compare students' actual and preferred perceptions of their classroom learning environments at the upper secondary and higher education levels. This study also examined differences in perceptions according to faculty and student expectations. A sample of 30 students participated in this study. The reliability of the modified CUCEI scale ranged from 0,28 to 0.88 for actual form and 0,65 to 0.94 for preffered form. When the two forms of instruments were compared, students in the first year of higher education had a perception of an actual learning environment that was less good than ideal in the cooperation dimension. Therefore, there is a need to improve the learning environment on the cooperation aspect.